The effect of gamma irradiation on the dielectric properties of polyethylene-based composites with the CdS/ZnS binary system - Mustafayev, I.I.; Melikova, S.Z.; Hajiyeva, E.G. (Physics and Chemistry of Solid State, 2024)
Polyethylene-based composites with the CdS/ZnS binary system were obtained with a component ratio of 10% CdS/ZnS; 30% CdS/ZnS; 50% CdS/ZnS. The temperature dependences of the dielectric constant (ε) and the tangent of the dielectric loss angle (tgδ) of samples of HDPE+CdS/ZnS composites irradiated with a dose of 100 kGy, 50 kGy, and 200 kGy were shown. The dependences of the dielectric constant and the tangent of the dielectric loss angle of HDPE+Cds/ZnS composites on the gamma-irradiation dose have been determined.